2007
DOI: 10.3168/jds.s0022-0302(07)72604-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ultra-High Pressure Homogenization on the Cheese-Making Properties of Milk

Abstract: The effects of single- or 2-stage ultra-high pressure homogenization (UHPH; 100 to 330 MPa) at an inlet temperature of 30 degrees C on the cheese-making properties of bovine milk were investigated. Effects were compared with those from raw, heat-pasteurized (72 degrees C for 15 s), and conventional homogenized-pasteurized (15 + 3 MPa, 72 degrees C for 15 s) treatments. Rennet coagulation time, rate of curd firming, curd firmness, wet yield, and moisture content of curds were assessed. Results of particle size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
83
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 26 publications
11
83
1
5
Order By: Relevance
“…The adsorption of caseins onto the fat globules has the following implications for cheese-making characteristics of milk: (1) casein surface area in milk is increased, but the amount of micellar casein is reduced; (2) two types of particles with a casein micelle surface layer exist: native casein micelles and casein-covered fat globules; (3) when adsorbed, casein micelles tend to spread over the surface of the fat globule and hence increase in effective surface area but with reduced surfacedensity of κ-casein. The rennet coagulation time (RCT) of unhomogenised milk is generally lower than that of homogenized milk [57,62,135,149]. This is probably related to the larger casein surface area in homogenized milk, as well as the lower surface density of κ-casein.…”
Section: Homogenization Of Cheese-milkmentioning
confidence: 95%
See 2 more Smart Citations
“…The adsorption of caseins onto the fat globules has the following implications for cheese-making characteristics of milk: (1) casein surface area in milk is increased, but the amount of micellar casein is reduced; (2) two types of particles with a casein micelle surface layer exist: native casein micelles and casein-covered fat globules; (3) when adsorbed, casein micelles tend to spread over the surface of the fat globule and hence increase in effective surface area but with reduced surfacedensity of κ-casein. The rennet coagulation time (RCT) of unhomogenised milk is generally lower than that of homogenized milk [57,62,135,149]. This is probably related to the larger casein surface area in homogenized milk, as well as the lower surface density of κ-casein.…”
Section: Homogenization Of Cheese-milkmentioning
confidence: 95%
“…The former increases the probability of interactions between particles, whereas the latter, for a subclass of particles, reduces the amount of κ-casein that needs to be hydrolyzed before micellar flocculation is induced. Conflicting reports exist on the influence of homogenization on the rate of rennet-induced gel formation; both homogenization-induced increases [57,62,149] and decreases [135] therein have been reported. Zamora et al [149] reported that, on high-pressure homogenization (100-330 MPa), the rate of gel formation may be either increased or decreased, with no clear trend as a function of homogenization pressure, but large differences in the pH of samples hinder a clear and unequivocal interpretation of these data.…”
Section: Homogenization Of Cheese-milkmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that denaturation of whey proteins is due to applied pressure and results in interaction between denatured whey protein and casein, which in turn increases the retention of former within casein matrix of cheese. Thus, these changes result in modifying the technological parameters of milk to make cheese, improving the rennet coagulation properties and yield of cheese (Trujillo et al 1999, San Martin-Gonzalez et al 2004, Zamora et al 2007.…”
Section: Application Of Hhp In Dairy Industrymentioning
confidence: 99%
“…3). Upon UHPH, these main peaks merge into a single peak between 0.1 and 0.3 lm depending on the homogenising pressure [93]. It has been observed that milk inlet temperature has a significant effect on the reduction of fat globule size [14,29,81].…”
Section: Particle Disruption and Food Stabilitymentioning
confidence: 98%